Beyond Simple Homology Searches: Multiple Sequence Alignments and Phylogenetic Trees. Issue 14 (2nd May 2017) - Zufall, Rebecca A.
Abstract: Phylogenetic trees represent hypotheses about evolutionary relationships between organisms or nucleotide or amino acid sequences. Because the best BLAST hit often does not represent the most closely related sequence, phylogenetic analyses are an essential extension of inquiry into any new protein or gene. In this unit, the reader will first learn how to create a multiple sequence alignment and then will learn how to use that alignment to build a neighbor‐joining phylogeny using the software program MEGA. Finally, the user will learn how to interpret a phylogeny in light of the research questions. © 2017 by John Wiley & Sons, Inc.